The Tree and the Water of Life - Jones, James (Anglican theological review, 2018)
The article presents a sermon by Church of England bishop James Jones delivered on April 2, 2017 at St. Paul's Cathedral in London, England. Topics include the experiences of poor people with environmental degradation, the connection of water with theological views of creation, and the role of water in the Bible.